Effective manual practices and wellness industry (Research Announcements "Heritage BG", 2025)
Ancient in origin, manual practices remain one of the most preferred and enjoyable procedures today. They are effectively involved in recovery, prevention, and even the treatment of various bodily imbalances. This article focuses on the systematization of heritage in the field of manual practices, as well as the possibilities for their application in various recreational procedures. This creates a foundation for developing educational programs in Wellness culture. An analysis is conducted on wellness innovations and good massage practices presented in the digital platforms of SPA and Wellness centres listed in the National Tourism Register.
Keywords: SPA and Wellness venues; certification; digital presentation; wellness education and trainings